Assessing the effectiveness of global protected areas based on the difference in differences model. (November 2021) - Feng, Yuhao; Wang, Yupin; Su, Haojie; Pan, Jiamin; Sun, Yuanfeng; Zhu, Jiangling; Fang, Jingyun; Tang, Zhiyao
Highlights: Effectiveness of global protected areas (PAs) was presented based on the difference-in-differences (DID) model. Changes in effectiveness over time were assessed with the help of long-time-series remote sensing data. Advantages of the DID model in assessing the effectiveness of PAs were confirmed. Abstract: Given the important role of protected areas (PAs) in biological conservation and the huge investment required to establish and manage them, it is essential to accurately assess the effectiveness of PAs. Previous studies typically used the difference between the PA and a non-protected area to measure the effectiveness and presented many space constraints to enhance the comparability between treatment and control groups. In contrast, however, researchers have given less consideration to time constraints, and there is still no consensus on the choice of period for assessing the effectiveness. Here, we explored this issue and assessed the effectiveness of 2, 975 PAs worldwide using the difference in differences (DID) model. We found that 56.2% of PAs were effective in maintaining plant productivity, and PAs in forests were more effective than those in non-forests. However, the effectiveness of PAs in improving ecological stability was limited. The stability rose only in the regions where PAs could effectively maintain plant productivity (e.g., needleleaf forest, woodland or Central Europe). Further, an event-study analysis showed that global PAs had been playing a positive and persistent role in maintaining plant productivity. In addition to providing these new assessment results, we compared the assessment results derived from different methods and confirmed that the impact of not using the DID model was greater than that of not using the propensity score matching (PSM) method. We therefore recommend the use of the DID model in future effectiveness assessments.